The relationship between directional area scattering factor and foliage clumping based on DSCOVR EPIC data over Australian TERN sites - Pisek, Jan; Odera, Catherine Akinyi; Erb, Angela; Marshak, Alexander; Knyazikhin, Yuri (Frontiers in Remote Sensing, 2025)
The Directional Area Scattering Factor (DASF) quantifies the fraction of visible canopy leaf area in a given direction and has demonstrated utility in characterizing vegetation structure. While traditionally applied to dense canopies under the assumption of a non-reflective background, its broader applicability remains under investigation. This brief research report presents the first, direct empirical assessment of the relationship between DASF and the clumping index (CI), which describes the non-random grouping of foliage within canopy structures. Using data from the Earth Polychromatic Imaging Camera (EPIC) onboard the DSCOVR satellite, we evaluate DASF and CI across a variety of Australian Terrestrial Ecosystem Research Network (TERN) sites representing diverse vegetation densities and structures. Complementary in situ digital hemispherical photography (DHP) and CI estimates are used to validate satellite observations. Our findings provide empirical support for previously modeled relationships between DASF and CI. The retrieval accuracy in sparse canopies is challenged by increased background influence, requiring either refined observation conditions or advanced correction techniques. Our results confirm the potential of DASF as a scalable structural vegetation metric, aiding the development and interpretation of remote sensing vegetation indices and supporting improvements in canopy structural parameter retrieval from spaceborne platforms.